Material Appearance Modeling: A Data-Coherent Approach - Dong, Yue.; Lin, Stephen; Guo, Baining; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
One of the most prominent goals of computer graphics is to synthesize imagery indistinguishable in appearance from the real world. This however has been a challenge to achieve due to the complex factors that determine the appearance of objects, as well as the broad range of appearances that a given object can exhibit. This book presents a general framework to address this problem based on the inherent coherency in the reflectance data of materials. This coherence-based approach can be comprehensively applied to all the major elements of image-based appearance modeling, from data acquisition and user-assisted modeling to efficient rendering and model editing. The techniques and underlying ideas in this book can benefit practitioners, researchers and students who wish to enhance the realism of their computer graphics imagery.
Introduction -- Surface Reflectance Overview -- Efficient SVBRDF acquisition with manifold bootstrapping -- Interactive SVBRDF Modeling from a Single Image -- Overview of Subsurface Light Transport -- Modeling subsurface light transport with the kernel Nystrom method -- Modeling and rendering subsurface scattering using diffusion equations -- Modeling textured translucent materials with lazy solid texture synthesis -- Overview of Material Fabrication -- Fabricating spatially-varying subsurface scattering -- Conclusion.
Keywords: Computer science; Computer graphics; Image processing; Computer Science; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Electronic books